Acupuncture and rehabilitation of the painful shoulder: study protocol of an ongoing multicentre randomised controlled clinical trial [ISRCTN28687220] - Vas, Jorge; Perea-Milla, Emilio; Mendez, Camila; Herrera Galante, Antonia; Madrazo, Fernando; Medina-Porqueres, Iván; Ortega, Caridad; Olmo, Victoria; Perez-Fernandez, Francisco; Hernandez, Luz; Seminario, Jose Maria; Brioso, Mauricio; et al. (BMC, 2005)
Background: Although the painful shoulder is one of the most common dysfunctions of the locomotor apparatus, and is frequently treated both at primary healthcare centres and by specialists, little evidence has been reported to support or refute the effectiveness of the treatments most commonly applied. In this study, we seek to evaluate the effectiveness of physiotherapy applied jointly with acupuncture, compared with physiotherapy applied with a TENS-placebo, in the treatment of painful shoulder caused by subacromial syndrome (rotator cuff tendinitis and subacromial bursitis). Methods/design: Randomised controlled multicentre study with blind evaluation by an independent observer and blind, independent analysis. A study will be made of 465 patients referred to the rehabilitation services at participating healthcare centres, belonging to the regional public health systems of Andalusia and Murcia, these patients presenting symptoms of painful shoulder and a diagnosis of subacromial syndrome (rotator cuff tendinitis and subacromial bursitis). The patients will be randomised into two groups: 1) experimental (acupuncture + physiotherapy); 2) control (TENS placebo + physiotherapy); the administration of rescue medication will also be allowed. The treatment period will have a duration of three weeks. The main result variable will be the change produced on Constant's Shoulder Function Assessment (SFA) Scale. A follow up examination will be made at 3, 6 and 12 months after the study period has ended. Discussion: The discussion will take into account the limitations of the study, together with considerations such as the choice of a simple, safe method to treat this shoulder complaint, the choice of the control group, and the blinding of the patients, evaluators and those responsible for carrying out the final analysis.
Keywords: Acupuntura; Hombros - Enfermedades; Acupuncture; Shoulder pain; Randomized clinical trial; Rehabilitation; Physiotherapy